DO INVESTORS VALUE ESG? EVIDENCE FROM INDONESIAN RETAIL INVESTORS - Aliya Izet Adrianto (Sean Institute, 2023)
The purpose of this study was to identify how the role of a stock's ESG rating can control the influence of investor motives—rational and irrational—on a company's performance expectations and risk level in the future. This study presents a structured online experimental method in measuring the effect of the interaction between investor motives and ESG ratings, and the main effect between these independent variables on issuers' performance expectations and risk levels. 3 x 2 between-subjects are performed to analyze the main effect, interaction effect, and also to test the research hypothesis. This study successfully manipulated ESG ratings. Furthermore, ESG ratings were found to lead to improvements in performance expectations and reduced expectations at risk levels. We minimize the impact of online data retrieval limitations. This study isolates the measurement of the interaction of investor motives to their influence on future performance expectations and risk levels, and the extent to which the relationship depends on ESG ratings.